Sazonalidade da concentração de metais no material particulado (MP10) por espectrometria de emissão óptica com plasma induzido - Scudeler, Ana Flávia (2024)
The disorderly growth in urban centers causes irreversible damage to the environment and human health. The issue related to air pollution has been an issue explored in recent decades, however, the lack of data in many regions makes it difficult to create adequate standards and quality standards. Studies have pointed out the association between particulate matter (PM) present in the atmosphere and respiratory tract diseases, especially affecting children and the elderly. These atmospheric particles can contain a variety of organic or inorganic groups, such as soot, metals or even biological material. It is relevant to analyze the concentration and chemical composition of PM to determine its effects on health, taking into account the seasonality of the collections. The objective of this study was to estimate the concentrations of metals present in particles with an aerodynamic diameter of less than 10 micrometers (PM10) in the atmosphere of the city of Francisco Beltrão in Paraná, thus contributing to the evaluation of air quality. Four campaigns of ten days each (24 consecutive hours) were carried out in the central region of the city, using a Large Volume Sampler (AGV-MP10) and fiberglass filters. Samples were collected according to seasonal patterns: fall 2021, winter 2021, spring 2021, and summer 2022. Of the 40 samples collected, all were in compliance with the standards established by the National Environmental Council (CONAMA No. 491/18), which is 120 μg m-3, however, eight specimens had values above the norms indicated by the World Health Organization (Who), which is 45 μg m-3. The sample with the highest concentration of PM was on 09/19/2021 (winter-spring) with a value of 66.6 μg m-3, and the sample with the lowest value was on 12/15/21 with 8.0 μg m-3, in spring-summer. Inductively coupled plasma optical emission spectrophotometry (ICP-OES) was used to determine the metals. The metals determined in MP10 were: Cd, Cr, Cu, Fe, Mn, Ni and Pb. Among the metals analyzed, iron was the one with the highest concentrations, with a seasonal average of 1.35 μg m-3 in autumn, 1.39 μg m-3 in winter, 0.82 μg m-3 in spring and 0.50 μg m-3 in summer, followed by chromium, which had a higher seasonal average concentration in winter of 0.05 μg m-3 and copper of 0.01 μg m-3 in autumn. The other metals did not have significant values during the analysis. The seasonal trend observed in the concentrations of PM and in most metals had higher values in the dry season (autumn, winter) and lower in the rainy season (spring, summer). The results show that the city of Francisco Beltrão has good air quality in relation to the parameters evaluated during the study period. However, the increase in vehicles using fossil fuels, the burning of wood as a common practice in the region can compromise this air quality.